Analysis of risk factors for ureteral stricture and tumor recurrence after transurethral resection of bladder tumor in paraureteral bladder cancer - Meng, Rui; Han, Yu; Zhai, Zhipeng (Frontiers in Surgery, 2025)
BackgroundThis study explores the risk factors for ureteral stricture and tumor recurrence after transurethral resection of bladder tumor (TURBT) in patients with paraureteral bladder cancer, aiming to provide references for clinicians in their treatment practices.MethodsA retrospective analysis was conducted on 164 patients with paraureteral bladder cancer who underwent TURBT from April 2017 to July 2024, among whom 133 patients had complete clinical data and follow-up data. Univariate and multivariate logistic regression analyses were used to identify the risk factors for ureteral stricture and tumor recurrence after TURBT in paraureteral bladder cancer.ResultsThe incidence of ureteral stricture after TURBT in patients with paraureteral bladder cancer was 11.28% (15/133), and the recurrence rate of bladder cancer within 1 year after surgery was 21.80% (29/133). Multivariate logistic regression analysis showed that diabetes mellitus (p = 0.021) and tumor diameter (p = 0.002) were independent risk factors for ureteral stricture within 1 year after TURBT. Additionally, multivariate logistic regression analysis revealed that sex (p = 0.021), diabetes mellitus (p = 0.008), and pathological T stage (p = 0.002) were independent risk factors for bladder tumor recurrence within 1 year after TURBT.ConclusionDiabetes mellitus and tumor diameter are independent risk factors for ureteral stricture within 1 year after TURBT in patients with paraureteral bladder cancer. Sex, diabetes mellitus, and pathological T stage are independent risk factors for bladder tumor recurrence within 1 year after TURBT in these patients.